2012
DOI: 10.1149/2.026302jes
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Fade Model for Spinel LiMn2O4Electrode

Abstract: A mathematical model for the capacity fade of a LiMn2O4 (LMO) electrode is developed in this paper by including the acid attack on the active material and the solid electrolyte interphase (SEI) film formation on the LMO particle surface. The acid generated by the LiPF6 and the solvent decompositions are coupled to the manganese (Mn) dissolution. The decrease of the Li ion diffusion coefficient is involved as another contribution to the capacity fade, which is caused by the passive film formation on the active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 45 publications
2
98
0
Order By: Relevance
“…7,9,[21][22][23][24] Previous studies have shown that such a model can predict experimental data adequately. 9,21,25,26 The model considers physical process changing along the electrode thickness direction of a Li-ion battery as illustrated in Figure 1a and diffusion process in the solid active material, which are coupled together through interfacial reaction.…”
Section: Model Development and Optimization Protocolmentioning
confidence: 99%
“…7,9,[21][22][23][24] Previous studies have shown that such a model can predict experimental data adequately. 9,21,25,26 The model considers physical process changing along the electrode thickness direction of a Li-ion battery as illustrated in Figure 1a and diffusion process in the solid active material, which are coupled together through interfacial reaction.…”
Section: Model Development and Optimization Protocolmentioning
confidence: 99%
“…This phenomenon is observed in all lithium-ion battery electrodes, but it is especially pronounced in the Si-based electrodes. 8,18 As the loading and thickness increase, both the ion-transport distance and tortuosity of the pores in the composite electrode increase. Thus, lithium ion diffusion is inhibited.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Y. Dai [16] introduces a mathematical model to simulate the stress in the LMO cathode particle. For lithium ion batteries with LMO cathode, a capacity fade model considering the manganese (Mn) dissolution is built by R. E. White [17]. However, mechanism models are very complicated, many parameters and massive calculation are involved.…”
Section: Introductionmentioning
confidence: 99%